DETERMINAN NET INTEREST MARGIN PERBANKAN NASIONAL: APLIKASI MODEL REGRESI DATA PANEL FIXED EFFECT - Zulkifli Z; Rispa Eliza (Universitas Mercu Buana, 2018)
The study aims to prove empirically the determinants of the performance of the net interest margin (NIM) ratio of banks listed on the Indonesia Stock Exchange (IDX) during the period 2005-2015 using the fixed effect panel data regression method with eleven banks selected as research samples. The results of the study found that the NPL, LDR, ROA, SBI, and Exchange Rate ratio significantly affected the NIM ratio performance. From the variables that significantly influence, the exchange rate variable is the most dominant variable, while the NPL ratio variable is the variable with the smallest influence. All independent variables, which consist of; CAR, NPL, LDR, BOPO, ROA, SBI, inflation, and exchange rates simultaneously affected the ratio of banking NIMs listed on the Indonesia Stock Exchange (IDX) during the period 2005-2015 significantly. Individually, the bank with the most sensitivity to changes in the NIM ratio is Bank International Indonesia Tbk (BII), while the least sensitive is Bank Victoria Indonesia Tbk (BVI)